Filtration and Finite-Dimensional Characterization of Logarithmically Convex Measures - Kulik, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study the classes C(α, β) and C H(α, β) of logarithmically convex measures that are a natural generalization of the notion of Boltzmann measure to an infinite-dimensional case. We prove a theorem on the characterization of these classes in terms of finite-dimensional projections of measures and describe some applications to the theory of random series.